2007
DOI: 10.1590/s0100-204x2007000800016
|View full text |Cite
|
Sign up to set email alerts
|

Esterase profile in the postembryonic development of Rhipicephalusmicroplus

Abstract: -The objective of this work was to analyze the pattern of esterase activity in the development stages of Rhipicephalus microplus by nondenaturing polyacrylamide gel electrophoresis using specific staining for esterase. The electrophoretical results revealed the presence of nine regions displaying esterase activity, stained with both alpha-naphthyl acetate and beta-naphthyl acetate, and classified as alpha-beta-esterase. Stage-specific esterases were found, with the first nymphal and larval stages showing the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…Whole tick extracts were used to get the maximum number of esterases. Though only three major bands were detected in whole tick extracts in this study rather many other bands detected in different stages of life cycle in different species of ticks by many other studies (Jamroz et al 2000;Villarino et al 2003;Baffi et al 2005Baffi et al , 2007 Al-Shammery and Fetoh 2011) but it clearly indicates about the sexual polymorphism in esterase expression in H. a. anatolicum ticks. Moreover, esterase activity is directly linked with acaricide resistance (Abbas et al 2014).…”
Section: Discussioncontrasting
confidence: 58%
“…Whole tick extracts were used to get the maximum number of esterases. Though only three major bands were detected in whole tick extracts in this study rather many other bands detected in different stages of life cycle in different species of ticks by many other studies (Jamroz et al 2000;Villarino et al 2003;Baffi et al 2005Baffi et al , 2007 Al-Shammery and Fetoh 2011) but it clearly indicates about the sexual polymorphism in esterase expression in H. a. anatolicum ticks. Moreover, esterase activity is directly linked with acaricide resistance (Abbas et al 2014).…”
Section: Discussioncontrasting
confidence: 58%
“…Similar profiles in resistant larval homogenate (IVRI-IV) were observed in the present study when stained with both anaphthyl and b-naphthyl acetate. Baffi et al (2007) reported four esterase bands in larvae without any correlation with resistance. Similarly, Miller et al (2007) could not correlate permethrin resistance with metabolic detoxification via synergistic as well as TPP based inhibitors study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that four CarE genes were expressed at >two‐fold higher levels in pupae than adults of Anopheles gambiae (Strode et al, ). The different expression profile of PCE2 between male and female mites has been detected, while the study in R. microplus has also found that an EST called EST‐4 was sex‐specific (Baffi et al, ).…”
Section: Discussionmentioning
confidence: 99%